The modernization of the western world - McGrath, John T., 1956- author.
1 online resource
Keywords: "Covering Western history from the ancient world to the current era of globalization, The Modernization of the Western World describes the forces of social change and what they have meant to the lives of the people caught up in them. The volume presents the history of Western civilization from a historical sociology perspective, introducing readers to the analyses of thinkers like Émile Durkheim, Karl Marx, Adam Smith, Ferdinand Tönnies, and Max Weber, in order to provide tools for understanding how societies function and change. This application of modernization theory argues, not that what has happened in the West should or even must happen in non-Western societies, but that understanding modernization as a process of social change affords a better understanding of why and how life has changed over the past millennium. The interactions of Western and non-Western societies have had a profound effect on each other; this is the story of the development of a truly global economy. This new edition has been updated to include a final chapter which addresses recent developments - economic disturbances in the global marketplace, cyberwarfare, and the rise of populist movements - testing the relevance of classic modernization theory for today. Featuring a glossary, maps and illustrations, boxed features, and an extensive index, this book will be of particular interest to students looking to understand world history as well as those interested in historical sociology and modernization theory"--